Pengaruh Metode Pembelajaran terhadap Kemampuan Mahasiswa dalam Menerapkan Model-Model Pembelajaran pada Perkuliahan Strategi Pembelajaran Matematika - Husnul Laili (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2017)
The research population comprised semester VI students of the mathematics study program of STIT Palapa Nusantara. The sample was selected using the purposive random sampling in three steps: (1) randomly selecting 2 classes out of 5 available classes, (2) selecting 8 groups, each consisting of 4 students, from each selected class, and (3) randomly selecting the groups applying each learning model. The data were analyzed using the T2 Hotellings multivariate test at the significance level of 5% (0.05) for two-tailed testing and the univariate test at the significance level of 0.025. The results of the data analysis are as follows. (1) There are different effects of the STAD-type cooperative learning method and the simulation learning method on students’ abilities in theory and application of learning methods in the mathematics strategy learning course (Fobserved = 6.76 > Ftable = F0.05;(2;65) = 3.14). (2) Abilities in theory of learning methods through the STAD-type cooperative learning method are higher than those through the simulation learning method in the mathematics learning strategy course (tobserved = 2.28 > ttable(0.025) = 2.00). (3) Abilities in application of learning methods through the simulation learning method are higher than those through the STAD-type cooperative learning method in the mathematics learning strategy course (tobserved = 4.05 >t table(0.025) = 2.00).